Metabolic profiling of mice plasma, bile, urine and feces after oral administration of two licorice flavonones. (15th July 2020) - Zhang, Lin; Wang, Chen-xiang; Wu, Jing; Wang, Tian-Yun; Zhong, Qiao-Qiao; Du, Yan; Ji, Shuai; Wang, Liang; Guo, Meng-Zhe; Xu, Sheng-Qiu; Tang, Dao-Quan
Abstract: Ethnopharmacological relevance: Licorice is an ancient food and medicinal plant. Liquiritigenin and liquiritin, two kinds of major flavonoes in licorice, are effective substances used as antioxidant, anti-inflammatory and tumor-suppressive food, cosmetics or medicines. However, their in vivo metabolites have not been fully explored. Aim of study: To clarify the metabolism of liquiritigenin and liquiritin in mice. Materials and methods: In this study, we developed a liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry approach to determine the metabolites in mice plasma, bile, urine and feces after oral administration of liquiritigenin or liquiritin. The structures of those metabolites were tentatively identified according to their fragment pathways, accurate masses, characteristic product ions, metabolism laws or reference standard matching. Results: A total of 26 and 24 metabolites of liquiritigenin or liquiritin were respectively identified. The products related with apigenin, luteolin or quercetin were the major metabolites of liquiritigenin or liquiritin in mice. Seven main metabolic pathways including (de)hydrogenation, (de)hydroxylation, (de)glycosylation, (de)methoxylation, acetylation, glucuronidation and sulfation were summarized to tentatively explain their biotransformation. Conclusion: This study not only can provide the evidence for in vivo metabolites and pharmacokinetic mechanism of liquiritigenin and liquiritin, but also may lay the foundation for further development and utilization of liquiritigenin, liquiritin and then licorice. Graphical abstract: Image 1 Highlights: Four LC-Q/TOF-MS/MS systems were respectively developed for mouse plasma, bile, urine and feces. In vivo metabolites of liquiritigenin and liquiritin in mice were first studied. A total of 26 and 24 metabolites of liquiritigenin and liquiritin in mice were identified. Oxidation and then methylation, glucuronidation and sulfation are the main metabolism pathways. Flavone or flavonol and its derivatives are the major metabolites of flavonones.